2014
DOI: 10.1007/s13277-014-2587-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based multiple-microRNA assay displays a better diagnostic performance than single-microRNA assay in the diagnosis of breast tumor

Abstract: Accumulating evidence has suggested that concentrations of blood-based circulating micro-ribonucleic acids (microRNAs, miRNAs) in breast tumor patients are significantly higher/lower than that in normal individuals, indicating that circulating miRNAs may serve as novel blood-based biomarkers for breast tumor. However, the results of previous studies on this issue have been inconclusive. Therefore, we perform a meta-analysis to determine whether aberrant miRNA expression can be used as molecular markers in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition, our metaanalysis showed that both plasma and serum could be recommended as clinical specimens. However, some previous meta-analyses showed plasma-based specimens had a higher accuracy than serum-based specimens, [45][46][47] while others provided opposite tendency, 48,49 further validation tests need to be conducted. 50 We also conducted a subgroup analyses based on the number of miRNAs being profiled.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, our metaanalysis showed that both plasma and serum could be recommended as clinical specimens. However, some previous meta-analyses showed plasma-based specimens had a higher accuracy than serum-based specimens, [45][46][47] while others provided opposite tendency, 48,49 further validation tests need to be conducted. 50 We also conducted a subgroup analyses based on the number of miRNAs being profiled.…”
Section: Discussionmentioning
confidence: 96%
“…Two characteristic examples include mir-21 and let-7a: both loci produce many abundant isomiRs in most of the studied TCGA datasets and all 32 cancer types. The miRNA molecules studied to date exhibit mixed expression patterns across tissues, which previously led to the proposed use of miRNA ‘panels’ as biomarkers (9092). …”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that these miRNAs are not adequately specific to be biomarkers (57). Such complications led several groups to suggest the use of "miRNA panels" as biomarkers rather than using one or a handful of miRNA molecules (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%